(untitled) (Research, Society and Development, 2022)
Breastfeeding is the best nutrition strategy, an affective bond in the mother/baby binomial, constituting a sensitive, economical and effective intervention in the reduction of infant morbidity and mortality. The hospitalization of a NB in ​​the NICU Neonatal Intensive Care Unit can make breastfeeding difficult, the breaking of the mother-baby binomial, the emotional exhaustion of the puerperal woman and the occurrence of breast engorgement due to weaning. The objective was to understand how Nursing care is provided in a situation of breast engorgement in puerperal women during the hospitalization of the Newborn in the NICU. This is an integrative review with an electronic search in the Virtual Health Library databases. Seven scientific articles were selected according to the inclusion and exclusion criteria of the research. The nursing team has an essential role in promoting and encouraging breastfeeding, in stimulating and guiding women, whether pregnant or postpartum women, thus preventing complications such as breast engorgement. It is essential to develop and follow standard care protocols (SOP) in nursing care, as well as constant reflection on practice and improvement of professionals’ knowledge to strengthen breastfeeding, reduce breast engorgement, as well as provide humanized care, technical-scientific, safe and quality treatment to women with babies hospitalized in the Neonatal ICU.